2015
DOI: 10.1097/nne.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Based Strategies for Promoting Clinical Reasoning Skills in Nursing Education

Abstract: Faculty face the demand of preparing nursing students for the constantly changing health care environment. Effective use of online, classroom, and clinical conferencing opportunities helps to enhance nursing students' clinical reasoning capabilities needed for practice. The growth of technology creates an avenue for faculty to develop engaging learning opportunities. This article presents technology-based strategies such as electronic concept mapping, electronic case histories, and digital storytelling that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…1 In the meantime, nursing education provides opportunities for students to create positive changes in a clinical setting. 2 Thus, the use of modern teaching approaches such as concept mapping (CM) in nursing can be useful. CM is designed based on the inclusion of crosslinks: learning occurs by establishing relationships or links between new concepts and themes and those already stored in the learner's cognitive structure.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the meantime, nursing education provides opportunities for students to create positive changes in a clinical setting. 2 Thus, the use of modern teaching approaches such as concept mapping (CM) in nursing can be useful. CM is designed based on the inclusion of crosslinks: learning occurs by establishing relationships or links between new concepts and themes and those already stored in the learner's cognitive structure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Barrett (2014) found that concept maps improved critical thinking skills as measured by the California Critical thinking skills Test. Lin, Han, Pan, and Chen (2014) found enhanced critical thinking with concept maps, and several authors (Moattari, Soleimani, Moghaddam, & Mehbodi, 2014;Shellenbarger & Robb, 2015;Williams-Brennan & Flynn-Post, 2015) found concept maps to be a valuable strategy for improving critical thinking and promoting clinical reasoning. In addition, Jaafarpour, Aazami, and Mozafari (2015) found higher mean scores on cumulative tests with groups of nursing students that created concept maps.…”
Section: Established (2011-2015)mentioning
confidence: 99%
“…The education and training methods that are intertwined with technology can be used to reflect the theoretical knowledge on nursing practices. The use of technology in nursing education offers many advantages for developing new teaching strategies (Axley, 2008;Shellenbarger and Robb, 2015). It is very important to integrate information technologies into the curriculum so that nursing students can achieve success during their education and professional career (Edwars and O'Connor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This situation has led to the emergence of new knowledge and concepts related to technology in nursing education, practices and researches. In addition, it also required for nurses to acquire new knowledge and skills in the changing application areas (Camilli, 2014;Chan et al, 2016;Shellenbarger and Robb, 2015). Along with the global technological developments, nursing faculties providing education at the undergraduate level are faced with the fact that students should be prepared for the changing health care environments (Shellenbarger and Robb, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation